Antagonism Activity of Phosphate Solubilizing Bacteria Against Ganoderma philippii and Fusarium oxysporum of Acacia Plants - Muhammad Asril; Yuni Lisafitri; Bayo Alhusaeri Siregar (Pandawa Institute, 2022)
Ganoderma philippii and Fusarium oxysporum 0148c are the primary pathogenic fungi that causes root rot and damping-off in young acacia plants. The best treatment to date is the use of biological control agents. Phosphate solubilizing bacteria (PSB) isolated from acid soil is a bacterial isolate classified as plant growth-promoting bacteria (PGPB). PGPB has an indirect function as a biocontrol agent for fungal pathogens. This study aimed to determine the potential of PSB isolate EF.NAP 8 in inhibiting G. philippii and F. oxysporum 0148c from acacia plants. The method used is a dual culture antagonism test and observation of abnormal hyphae after the antagonism process. The results showed that the isolate EF.NAP 8 inhibited G. philippii by 34.44% and F. oxysporum 0148c by 33.33%. The abnormality of hyphae after antagonistic activity results in hyphal malformations such as hyphae lysis and hyphae coiling. The antagonistic activity of PSB EF.NAP 8 isolate is one of part of the ability of a bacterium classified as PGPB in the form of biocontrol activity against pathogenic fungi. This provides information regarding the opportunity to utilize EF.NAP 8 as a candidate agent for controlling fungal pathogens on acacia plants.